![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) 7(x-5)+14=56
<=>7(x-5)=42
<=>x-5=6
<=>x=11
b)9(x+1)-3=15
<=>9(x+1)=18
<=>x+1=2
<=>x=1
c)12(x+5)-36=48
<=>12(x+5)=84
<=>x+5=7
<=>x=2
d)5(x+14)=145
<=>x+14=29
<=>x=15
![](https://rs.olm.vn/images/avt/0.png?1311)
a) 100 - 7.(x-5) = 68
7.(x - 5) = 100 - 68 = 32
x - 5 = \(\frac{32}{7}\)
x = \(\frac{32}{7}+5=\frac{67}{7}\)
b) 2(x-6)+2227:17=151
2( x -6) + 131 = 151
2 (x - 6) = 20
x - 6 = 20 : 2 = 10
x = 10 + 6 = 16
![](https://rs.olm.vn/images/avt/0.png?1311)
a ) \(\left(19x+2,5^2\right)\div14=\left(13-8\right)^2-4^2\)
\(\Rightarrow\left(19x+50\right)\div14=5^2-16\)
\(\Rightarrow\left(19+50\right)\div14=25-16=9\)
\(\Rightarrow19x+50=9\times14\)
\(\Rightarrow19x+50=126\)
\(\Rightarrow19x=126-50\)
\(\Rightarrow19x=76\)
\(\Rightarrow x=4\)
b ) \(1440\div\left[41-\left(2x-5\right)\right]=2^4.3\)
\(\Leftrightarrow1440\div\left[41-\left(2x-5\right)\right]=48\)
\(\Leftrightarrow41-\left(2x-5\right)=30\)
\(\Leftrightarrow2x-5=11\)
\(\Leftrightarrow2x=16\)
\(\Leftrightarrow x=8\)
![](https://rs.olm.vn/images/avt/0.png?1311)
1 / 5 x 2 2 + ( x + 3 ) = 5 2
20 + ( x + 3 ) = 25
x + 3 = 5
x = 2
2 / 3 2 x 2 + ( x + 25 ) = 10 2
18 + ( x + 25 ) = 100
x + 25 = 82
x = 57
3 / 2 3 x 5 - ( x + 3 2 ) = 10
40 - ( x + 9 ) = 10
x + 9 = 30
x = 21
4 / 7 2 - 7 x ( 13 - x ) = 14
49 - 7 x ( 13 - x ) = 14
7 x ( 13 - x ) = 35
13 - x = 5
x = 8
5 / 14 x - 2 x 7 2 = 2 x 3 x 7
14 x - 98 = 42
14 x = 140
x = 10
1/ 5 x 22 + ( x + 3 ) = 52
2/ 32 x 2 + ( x + 25 ) = 102
3/ 23 x 5 - ( x + 32 ) = 10
4/ 72 - 7 x ( 13 - x ) = 14
5/ 14x - 2 x 72 = 2 x 3 x 7
1 / 5 x 2 2 + ( x + 3 ) = 5 2
20 + ( x + 3 ) = 25
x + 3 = 5
x = 2
2 / 3 2 x 2 + ( x + 25 ) = 10 2
18 + ( x + 25 ) = 100
x + 25 = 82
x = 57
3 / 2 3 x 5 - ( x + 3 2 ) = 10
40 - ( x + 9 ) = 10
x + 9 = 30
x = 21
4 / 7 2 - 7 x ( 13 - x ) = 14
49 - 7 x ( 13 - x ) = 14
7 x ( 13 - x ) = 35
13 - x = 5
x = 8
5 / 14 x - 2 x 7 2 = 2 x 3 x 7
14 x - 98 = 42
14 x = 140
x = 10
nhé !
![](https://rs.olm.vn/images/avt/0.png?1311)
\(a,\left(7x-11\right)^3=2^5.5^2+200.\)
\(\left(7x+11\right)^3=32.25+200.\)
\(\left(7x+11\right)^3=800+200.\)
\(\left(7x-11\right)^3=1000.\)
\(\left(7x-11\right)^3=10^3.\)
\(\Rightarrow7x-11=10.\)
\(\Rightarrow x=\left(10+11\right):3=7\in Z.\)
Vậy.....
\(b,3^x+25=26.2^2+2.3^0.\)
\(3^x+25=26.4+2.\)
\(3^x+25=104+2.\)
\(3^x+25=106.\)
\(3^x=106-25.\)
\(3^x=81.\)
\(3^x=3^4\Rightarrow x=4\in Z.\)
Vậy.....
\(c,2^x+3.2=64.\)(có vấn đề).
\(d,5^{x+1}+5^x=750.\)
\(5^x.5^1+5^x+1=750.\)
\(5^x\left(5^1+1\right)=750.\)
\(5^x\left(5+1\right)=750.\)
\(5^x.6=750.\)
\(5^x=750:6.\)
\(5^x=125.\)
\(5^x=5^3\Rightarrow x=3\in Z.\)
Vậy.....
\(e,x^{15}=x.\)
\(\Rightarrow x\left(x^{14}-1\right)=0\Rightarrow\left\{{}\begin{matrix}x=0\\x=1\end{matrix}\right..\)
\(f,\left(x-5\right)^4=\left(x-5\right)^6.\)
\(\Leftrightarrow\left(x-5\right)^4-\left(x-5^6\right)=0.\)
\(\Leftrightarrow\left(x-5\right)^4\left[1-\left(x-5\right)^2\right]=0.\)
\(\Leftrightarrow\left(x-5\right)^4\left(1-x+5\right)\left(1+x-5\right)=0.\)
\(\Leftrightarrow\left(x-5\right)^4\left(6-x\right)\left(x-4\right)=0.\)
\(\Leftrightarrow\left(x-5\right)^4=0\Rightarrow x-5=0\Rightarrow x=5\in Z.\)
\(6-x=0\Rightarrow x=6\in Z.\)
\(x-4=0\Rightarrow x=4\in Z.\)
Vậy.....
![](https://rs.olm.vn/images/avt/0.png?1311)
Mình xin giải như sau:
a)15x-57=3^14:3^9
15.x-57=3^5
15.x-57=243
15.x=243+57
15.x=300
x=300:15
x=20
b)50-[70:(x-1)]=15
70:(x-1)=50-15
70:(x-1)=35
x-1=70:35
x-1=2
x=2+1
x=3
c) (5^2+2^3).x+4^2=7^2
(25+8).x+16=49
33.x=49-16
33.x=33
x=33:33
x=1
d) 2^x:2^5=1
2^x=1.2^5
2^x=2^5
Suy ra x=5
18-(x-2)^5=2.3^2
18-(x-2)^5=2.9
18-(x-2)^5=18
(x-2)^5=18-18
(x-2)^5=0
x=0+2
x=2
![](https://rs.olm.vn/images/avt/0.png?1311)
a) (x-51)=2.8+20 b) 4.(x-3) = 49-1 c) 2x-49=5.27 d) 9.(x+4)-25=5.4
x-51 =16+20 4.(x-30)=48 2x-49=135 9.(x+4)-25=20
x-51 =36 x-30=48:4 2x =135+49 9.(x+4) =20+25
x = 36+51 x-30= 12 2x =184 9.(x+4) =45
x = 87 x =12+30 x=42 x =184:2 x= 92 x+4 =45:9
x+4 =5
x =5-4 x=1
32 ( x + 14 ) - 52 = 5 x 22
9 ( x + 14 ) - 25 = 5 x 4
9( x +14 ) - 25 = 20
9 ( x +14 ) = 45
x + 14 = 5
x = -9
32 ( x+ 14 ) - 52 = 5 x 22
9 ( x + 14 ) - 25 = 20
9( x + 14 ) = 20 + 25 = 45
x + 14 = 45 : 9 = 5
x = 5 - 14 = -9
chúc học tốt